Proceedings of the 1989 IEEE Particle Accelerator Conference, . 'Accelerator Science and Technology
DOI: 10.1109/pac.1989.73053
|View full text |Cite
|
Sign up to set email alerts
|

Studies of ferrite materials for the AGS Booster Synchrotron

Abstract: Its accelerating cavities are sveep-tuned by varying the permeabilitv of ferrite core rings vithin the cavities. Core material selection criteria and evaluation are discussed Measure-Tents of permeability, loss and perrni tt i" : ty .v.c presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…During the initial stages of this coalescing upgrade, a literature search revealed that newer types of NiZn ferrites were commercially available with significantly lower high field losses [4]. A decision was made to test several of these new ferrites to determine their properties and high field losses at 2.5 and 5 MHz.…”
Section: Ferrite Selection and Testingmentioning
confidence: 99%
“…During the initial stages of this coalescing upgrade, a literature search revealed that newer types of NiZn ferrites were commercially available with significantly lower high field losses [4]. A decision was made to test several of these new ferrites to determine their properties and high field losses at 2.5 and 5 MHz.…”
Section: Ferrite Selection and Testingmentioning
confidence: 99%
“…This also saves some ring space. Assuming type 4M2 ferrite [2,3,4] with 60 cm OD and 30 cm ID rings we would fill the two lowest frequency cavities with 1.26 meters of ferrite, the amount needed to keep the B field below 200 gauss at 1.5 MHz. The remaining higher harmonic cavities would be filled with 0.87 meters of femte.…”
Section: Hi Rf Cavitymentioning
confidence: 99%